ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI TINGKAT PENERAPAN AKUNTANSI AKRUAL PADA PEMERINTAH - Muhamad Indra Yudha Kusuma; Fuad Fuad (Diponegoro Journal of Accounting, 2013)
This study aims to provide an overview and empirical evidence on the level of implementation of accrual accounting in government, especially at the work units and examine the various factors that exist in the work units from human factors, organizational factors, and other situational factors thought to have an influence on the level implementation of accrual accounting.Data collection in this study using a questionnaire survey. The questionnaire was delivered to 156 Managers/Kuasa Pengguna Anggaran (KPA) of the government institusion in the region of KPPN Semarang I. A total of 58 questionnaires were returned and 49 questionnaires (31.41%) complete and can be processed. The data collected were processed using multiple linear regression analysis.The results of this study indicate that the implementation of accrual accounting in government is still very low. In particular, the level of implementation of accrual accounting is significantly affected by the financial staff training. However, there are no significant effect of level of education staff, the quality of information technology, consulting support, experience, educational background of the managers and the size of the work units to the level of implementation of accrual accounting.